PENGEMBANGAN KOMIK EDUKASI BERBASIS CREATIVE PROBLEM SOLVING BERBANTUAN KVISOFT FLIPBOOK MAKER PRO UNTUK SEKOLAH DASAR - Dina Dahliana; Wulan Oktavia; Yola Marsanda; Rahmi Indah Cahyani (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
This research aims to develop and produce the effectiveness of an educational comic based on Creative Problem Solving (CPS) using Kvisoft Flipbook Maker Pro as interactive media for elementary school students. This research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model development approach. The main innovation of this research is the use of the Creative Problem Solving approach in designing educational comic content. In addition, Kvisoft Flipbook Maker Pro is used to present comics interactively, adding a more interesting visual dimension. The research results include educational comics developed and evaluation results from field trials. Evaluation involves responses from students, teachers, and the appropriateness, attractiveness, and effectiveness of comics in increasing understanding of educational concepts. It is hoped that this research can contribute to the development of innovative teaching methods and increase student involvement in the learning process. The results obtained were that the teaching materials developed obtained a validity percentage of 89.06% (Content Validation), 80% (Graphic Validation), and 83.3% (Language Validation). The practicality of the teacher's response was obtained at 3.7 (very practical), while the student's response was 3.5 (very practical. Effectiveness can be seen from student learning outcomes, namely an N-Gain Score of 0.71 (High) in the quite effective category. This means, The teaching materials developed are valid, practical and effective for grade 3 elementary school students